Antibody profiles in COVID‐19 convalescent plasma prepared with amotosalen/UVA pathogen reduction treatment. Issue 3 (12th February 2022) - Bagri, Anil; de Assis, Rafael R.; Tsai, Cheng‐Ting; Simmons, Graham; Mei, Zhen W.; Von Goetz, Melissa; Gatmaitan, Michelle; Stone, Mars; Di Germanio, Clara; Martinelli, Rachel; Darst, Orsolya; Rioveros, Jowin; et al.
Abstract: Background: COVID‐19 convalescent plasma (CCP), from donors recovered from severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection, is one of the limited therapeutic options currently available for the treatment of critically ill patients with COVID‐19. There is growing evidence that CCP may reduce viral loads and disease severity; and reduce mortality. However, concerns about the risk of transfusion‐transmitted infections (TTI) and other complications associated with transfusion of plasma, remain. Amotosalen/UVA pathogen reduction treatment (A/UVA‐PRT) of plasma offers a mitigation of TTI risk, and when combined with pooling has the potential to increase the diversity of the polyclonal SARS‐CoV‐2 neutralizing antibodies. Study design and methods: This study assessed the impact of A/UVA‐PRT on SARS‐CoV‐2 antibodies in 42 CCP using multiple complimentary assays including antigen binding, neutralizing, and epitope microarrays. Other mediators of CCP efficacy were also assessed. Results: A/UVA‐PRT did not negatively impact antibodies to SARS‐CoV‐2 and other viral epitopes, had no impact on neutralizing activity or other potential mediators of CCP efficacy. Finally, immune cross‐reactivity with other coronavirus antigens was observed raising the potential for neutralizing activity against other emergent coronaviruses. Conclusion: The findings of this study support the selection of effective CCP combined with the use of A/UVA‐PRT in the production of CCP for patients with COVID‐19.